Legitimating accounting change in charities: when values count more than regulation. Issue 1 (13th November 2020) - Connolly, Ciaran; Hyndman, Noel; Liguori, Mariannunziata
Abstract : Purpose: This paper seeks to explore the way charity accountants understand, interpret and legitimate or delegitimate the introduction of accounting and reporting changes (embedded in the extant charity statement of recommended practice), before these are actually implemented. Design/methodology/approach: Drawing on 21 semi-structured interviews with accountants in large UK and Republic of Ireland charities, the manner and extent to which forthcoming changes in charity accounting are legitimated (justified) or delegitimated (criticised) is explored. Findings: Acceptance of accounting changes in the charity sector by formal regulation may not be necessary for future required adjustments to practice to be legitimated. Using interviews carried out before the implementation of required changes, the results suggest that other factors, such as national culture, identity and mimetic behaviours, may play a major role in the homogenisation and acceptance of accounting and reporting rules. In particular, it is argued that mimetic pressures can be much more influential than regulative pressures in legitimating change in the charity sector and are more likely to lead to the embedding of change. Originality/value: The contribution of this paper is threefold. First, it explores rhetoric and legitimation strategies used before changes are actually implemented. Second, it contributes to filling a gap in charities' research related to intra-organisational legitimation of managerial and accounting changes, illustrating institutional-field identity at work to preserve shared organisational values and ideas. Finally, the research illuminates the importance of particular contextual pressures and individual legitimation arguments during accounting-change processes.